2002
DOI: 10.1111/j.1748-5827.2002.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma (botryoid sarcoma) of the urinary bladder in a Maltese

Abstract: A urinary bladder tumour was diagnosed in a two-year-old female Maltese with haematuria and pollakiuria on the basis of ultrasonography and pneumocystography findings. The mass was resected, and the bladder was preserved at surgery. Histological and immunohistochemical examination confirmed the tumour to be a rhabdomyosarcoma, which has rarely been reported in small breeds of dog. There was no recurrence of the tumour at the original site in the urinary bladder two months later, when the dog died due to metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 8 publications
1
25
0
3
Order By: Relevance
“…In our case it was also a large breed dog -a Hovawart. Considering the age of affected animals, rhabdomyosarcomas are reported in young dogs of about 2 years (Yanoff et al 1996;Takiguchi et al 2002;Kuwamura et al 1998;Kim et al 1996;Illanes 2002). This fact corresponds to data from the human medicine on the occurrence of the rhabdomyosarcoma in children and adolescents (Illanes 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case it was also a large breed dog -a Hovawart. Considering the age of affected animals, rhabdomyosarcomas are reported in young dogs of about 2 years (Yanoff et al 1996;Takiguchi et al 2002;Kuwamura et al 1998;Kim et al 1996;Illanes 2002). This fact corresponds to data from the human medicine on the occurrence of the rhabdomyosarcoma in children and adolescents (Illanes 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of the rhabdomyosarcoma (bothryoid sarcoma) in the urinary bladder has relatively frequently been reported (Takiguchi et al 2002;Kuwamura et al 1998;K i m et al 1996). Many authors reported occasional cases of finding the rhabdomyosarcoma in the heart atrium and chamber (Krotje et al 1990;Gonin-Jmaa et al 1996;Perez et al 1998), perineal area (Ueno et al 2002), parameningeal area (Illanes 2002), tongue (Lascelles et al 1998), gingiva (Kim et al 1996) or greater omentum (Sarnelli et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…40 Botryoid rhabdomyosarcoma has been observed to occur in large breed dogs younger than 18 months but can occur in other dogs. [41][42][43][44][45][46][47][48][49][50] Botryoid rhabdomyosarcomas are embryonic mesenchymal tumors arising from pleuripotent stem cells originating from primitive urogenital ridge remnants. They are infiltrating tumors arising from the trigone and projecting into the bladder lumen as botryoid (resembling a cluster of grapes) masses.…”
Section: Primary Urinary Bladder Neoplasiamentioning
confidence: 99%
“…Puede haber fagocitosis por las células tumorales y reacción inflamatoria moderadamente densa. Se evidenció una mayor frecuencia de casos en canes machos (57.8%); sin embargo, no hay estudios que indiquen una predisposición del rabdomiosarcoma al sexo, con excepción del tipo botrioide de la vejiga urinaria en perros, el cual se presenta en una proporción de hembra/macho de 2:1 (Hulland, 1990;Takiguchi et al, 2002).…”
Section: Pleomórficounclassified